The Role of National Diversity Forum of Jakarta Province in the Implementation of National Diversity Implementation Policy - Kuswandi, Pepen; Sutrisno, Edy; Istania, Ratri (Universitas Teuku Umar, 2025)
The National Renewal Forum strengthens social harmony, facilitates intergroup dialogue to resolve conflicts, and encourages the implementation of multicultural values in Indonesia. This study aims to understand the role of the FPK of DKI Jakarta Province in implementing the policy of organizing national integration, identify the leading causes of the implementation of the policy of organizing national integration that is not optimal, and formulate strategies that can increase the effectiveness of the implementation of the policy of organizing national integration. This study uses a qualitative method with a case study approach, conducted at the National Renewal Forum (FPK) of DKI Jakarta Province as the research location. The data in this study were obtained through participatory observation, in-depth interviews, and documentation. The findings of this study are the DKI Jakarta National Integration Forum (FPK) has a strategic role as a facilitator of national integration, especially in maintaining cross-cultural interactions in a diverse society. The conclusion is the role of FPK has not been optimal due to several main obstacles: individual quality, budget constraints, lack of support from the board of trustees, ineffective internal interactions, lack of publication of the role of FPK, and lack of implementation of the main tasks of FPK.